Terorisme dan Komunitas Muslim - Sidik, Hasbi (Sosiologi: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2015)
Terrorism and Muslim Community are two inseparable issues nowdays. The papers focus on relation between both of them. After elaborating important terms, paper will show that the emergence of muslim community as terrorist actor is an integral series of triangle terrorism. Paper also discussed the approach used by muslim community namely hard approach and soft approach. The main argument is the Muslim community does not effectively combat terrorism.Keywords: Triangle terrorism, muslim community